The Influence of Anton Chekhov on Samuel Beckett: Inaction and Investment of hope into Godot-like Figures in Three Sisters and Waiting for Godot - Sasani, Samira; Ghasemi, Parvin (k@ta: A Biannual Publication on the Study of Language and Literature, 2012)
Anton Chekhov has been very much influential on modern drama, especially on the Theatre of the Absurd; however, not much work has been done on his influence on the absurdist playwrights. Considering Harold Bloom’s definition of ‘influence’—writing “much like” someone in the past—the seminal influence of Chekhov on Beckett is studied in this article. Chekhov in his plays, especially his major plays, very much like Beckett’s waiting for Godot, portrays people who are passively waiting and investing their entire hope into Godot-like figures without taking any action. Thus, the sense of ennui, desperation and consequently disappointment of these characters originates from their unreasonable inaction, stagnancy and their passivity while waiting, rather than ‘waiting for Godot figures’. This article tries to show the influence of Chekhov on Samuel Beckett, investigating the similarities in form, atmosphere and theme between Waiting for Godot, the paradigm of the Theatre of the Absurd, and Three Sisters, one of Chekhov’s major plays